Timing of the magmatic activity and upper crustal cooling of differentiated asteroid 4 Vesta. (15th March 2020) - Jourdan, F.; Kennedy, T.; Benedix, G.K.; Eroglu, E.; Mayer, C.
Abstract: Eucrites are extraterrestrial basalts and cumulate gabbros formed, and subsequently more or less metamorphosed, at the crustal level of the HED (Howardite-Eucrite-Diogenite) parent body, thought to be the asteroid 4 Vesta. Unbrecciated eucrites offer the best way to understand the igneous, metamorphic and cooling processes occurring in the crust of Vesta following accretion since they were not substantially affected/altered by secondary impact processes. The 40 Ar/ 39 Ar system of unbrecciated eucrites should be in a relatively pristine state, and thus can inform us on the early volcanic and thermal history of the HED parent body, and, in particular, the cooling history of various crustal parts below the ∼300 °C isotherm, which represents the average closure temperature of the Ar diffusion in plagioclase. We analysed plagioclase and pyroxene (± groundmass) separates of two cumulate (Moore County and Moama), and five (Caldera, BTN 00300, EET 90020, GRA 98098, QUE 97053) equilibrated basaltic eucrites with the 40 Ar/ 39 Ar technique using a Thermo© ARGUS VI multi-collection mass spectrometer. The two cumulate unequilibrated gabbros also gave cooling ages of 4531 ± 11 Ma and 4533 ± 12 Ma and combined with a fast cooling rate estimated from lamella thicknesses, suggest that magmatic activity persisted up to 4533 ± 11 and 4535 ± 12 Ma and that the plutons were intruded in a relatively shallow part of the crust, above the metamorphosed regions. Four equilibrated eucrites yielded a well-defined cluster of ages between 4523 ± 8 Ma to 4514 ± 6 Ma. Those ages indicate when the part of the upper crust, where those eucrites probably resided (∼10–15 km deep), cooled below ∼300 °C at a rate of 17.3 ± 3.6 °C/Ma (2σ). Such a slow cooling rate combined with available global thermal models, supports the hypothesis of a global crustal metamorphism by burial and reheating of lava flows. Finally, an age of 4531 ± 5 Ma was obtained for metamorphosed eucrite EET 90020 and, combined with petrographic observations, indicates the age of a major crustal excavation event by impact. 40 Ar diffusion models suggest that it is possible to differentiate impact vs crustal cooling provided that a sufficient quantity of pyroxene is measured by 40 Ar/ 39 Ar.